Group B. Consensus paper. Non-surgical periodontal therapy: mechanical debridement, antimicrobial agents and other modalities - Corbet, Esmonde; Ding, Yi; Emingil, Gulnur; Faveri, Marcelo; Humagain, Manoj; Izumi, Yuichi; Kamil, Wisam Alaa; Kemal, Yulianti; Mahanonda, Rangsini; Rajpal, Jaisika; Sakellari, Daimitra; Tan, Wah Ching; et al. (FDI World Dental Press Ltd, 2015)

(untitled)
Periodontal diseases are complex opportunistic infections modified by the host inflammatory response. Therefore, the current recommended treatment of periodontitis is primarily anti-infective in nature. Antiinfective approaches rely on adequate patient removal of plaque through good oral hygiene practices and mechanical debridement by an oral health professional. Scaling and root planing (SRP) is accepted to be the basis for all periodontal therapy, and any additional therapies should be considered adjunctive and supplemental.